2016
DOI: 10.29063/ajrh2016/v20i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Providers’ Experiences and Perceptions of LongActing Reversible Contraception in Lilongwe, Malawi

Abstract: Less than 2% of Malawian women use long-acting reversible contraception (LARC). We describe experiences of Malawian family planning providers, focusing on LARC. We conducted a mixed-methods study using questionnaires and focus group discussions with providers in Lilongwe. Data were analyzed separately and triangulated. Most (58%) participants saw over 30 patients daily. Only 19% had ever inserted IUC. Qualitative data were complementary; participants noted that LARC provision was important, though hindered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Findings from 12 countries in sub-Saharan African including Tanzania reported that hormonal implants were the first or second most widely used in 10 out of 12 countries studied compared with IUDs, pills and injectables [ 19 ]. The low use of IUDs could be explained by perceived misconceptions such as fear of abdomen pain, discomfort during sex and myth that IUDs can move into the abdomen during sexual intercourse [ 20 ]. Our finding is in contrast with previous study in rural China where the authors found that majority reported using IUDs than implants [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from 12 countries in sub-Saharan African including Tanzania reported that hormonal implants were the first or second most widely used in 10 out of 12 countries studied compared with IUDs, pills and injectables [ 19 ]. The low use of IUDs could be explained by perceived misconceptions such as fear of abdomen pain, discomfort during sex and myth that IUDs can move into the abdomen during sexual intercourse [ 20 ]. Our finding is in contrast with previous study in rural China where the authors found that majority reported using IUDs than implants [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skilled healthcare providers are critical in family planning programs to meet the supply‐side needs for family planning provision. Inadequately trained staff could be a barrier to the provision of family planning, especially LARC . Therefore, the present intervention included staff training and on‐the‐job mentoring after the courses to ensure the staff became competent.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that most urban women in Malawi aged 40 years and above have already attained their desired fertility, and would therefore like to use long-acting and permanent methods (LAPMs) to stop childbearing. Yet, short-term methods such as pills and injectables which are prone to discontinuation and may not satisfy the peculiar needs of these women are still the dominant modern contraceptive methods in Malawi, with less than 10% of all contraceptive users relying on LAPMs (32,33). One study in the capital of Malawi, Lilongwe, found that majority of the FP clinics did not offer IUD or female sterilization services (33).…”
Section: Discussionmentioning
confidence: 99%